Russian philosophy and circus art - Markov Alexander Viktorovich (Studia Humanitatis, 2022)
The leading Russian culture philosophers of the 20th century – Aleksei Losev and Gustav Shpet turned to images of circus art and eccentrics in order to explain how modern aesthetic perception works. The author proves that this appeal was not only illustrative, but had to structure the idea of culture in a new way, far from the habits of the positivist approach. Direct competition, which encourages subjective emotion and allegorical thinking, was questioned with the ascetic of contemplation and direct reaction, intended to the rules more than to properties. The ascetic of contemplation and direct reaction, which intends to the rules more than to properties, were set in opposition to the direct competition that encourages subjective emotion and allegorical thinking.